Digital Literacy Through The Tiktok Application As A Learning Material To Improve The Quality Of Students’ Learning - Sitanggang, Anita; Hutabarat, Novra Melisa P.; Nababan, Irene Adryani; Pandiangan, Ferda; Rumahorbo, Leta Denarosana; Sinambela, Rohanna; Simanjuntak, Naomi; Simatupang, Gracia Elizabeth (Journal Of Human And Education (JAHE), 2024)
The aim of this research is to determine the effectiveness of using the TikTok application as a learning medium in improving learning outcomes for students at SMA N 2 BANDAR. The research used a descriptive survey. The data collection technique uses a questionnaires to find out data on student learning outcomes. The collected data is then analyzed using quantitative analysis. The population in this research were all students in class follow offline learning materials for English subject at SMA N 2 BANDAR. The research results show that in the conventional learning process the learning outcomes obtained by students still get scores below the KKM. However, the use of TikTok as a learning medium succeeded in increasing the achievement of KKM scores. Therefore, it can be concluded that using TikTok as a learning medium can improve learning outcomes by considering the relevance of the material to be delivered.